Analysis of the Public Service Agency (BLUD) System on the Management of the Health Center Budget in the City of Cilegon - Novita Ambar Uma; Bambang Setiaji; Ratih Purnamasari (Eduvest - Journal of Universal Studies, 2026)
The implementation of the Regional Public Service Agency Financial Management Pattern (PPK-BLUD) in community health centers aims to improve the flexibility and effectiveness of service management. However, its impact on overall managerial performance has not been widely evaluated. This study aims to analyze the Regional Public Service Agency (BLUD) system in relation to budget management at community health centers in Cilegon City and to provide evidence-based policy recommendations. This study is qualitative, using in-depth interviews with informants at nine community health centers. Data were collected through in-depth interviews, observations, exploratory questionnaires, and document reviews. Data validity was strengthened through manual triangulation of sources and methods and analyzed using the Miles and Huberman model. Most health centers demonstrated financial efficiency and effectiveness above 90%. However, there were no new service innovations, service quality remained in the “good” category, and human resource training averaged below 30% of the total healthcare workforce. A gap exists between actual and ideal performance in BLUD implementation. To address this, it is necessary to strengthen performance-based financial management, improve a service culture oriented toward public satisfaction, develop service innovations, and plan human resource training based on all employees' needs. BLUD implementation has shown progress in financial efficiency but has not yet been optimal in terms of new service innovations and human resource development. The Balanced Scorecard (BSC) approach can serve as a strategic evaluative tool to drive managerial transformation at health centers.